Treatment and Prevention of Lung Cancer Using a Virus-Infected Reprogrammed Somatic Cell-Derived Tumor Cell Vaccination (VIReST) Regime - Zhang, Zhe; Lu, Shuangshuang; Dunmall, Louisa S. Chard; Wang, Zhizhong; Cheng, Zhenguo; Zhang, Zhongxian; Yan, Wenli; Chu, Yongchao; Gao, Dongling; Wang, Na; Li, Yang; Wang, Jiwei; et al. (Frontiers in Immunology, 2020)
Lung cancer is one of the most commonly diagnosed cancer and despite therapeutic advances, mortality remains high. The long period of clinical latency associated with lung cancer provides an ideal window of opportunity to administer vaccines to at-risk individuals that can prevent tumor progression and initiate long-term anti-tumor immune surveillance. Here we describe a personalized vaccination regime that could be applied for both therapeutic and prophylactic prevention of lung cancer, based on the derivation of lung cancer cells from induced pluripotent stem cells. Stem cells from healthy mice were modified to express Cre-dependent KRASG12D and Trp53R172H prior to differentiation to lung progenitor cells. Subsequent viral delivery of Cre caused activation of exogenous driver mutations, resulting in transformation and development of lung cancer cells. iPSC-derived lung cancer cells were highly antigenically related to lung cancer cells induced in LSL-KRASG12D/+; Trp53R172H/+ transgenic mice and were antigenically unrelated to original pluripotent stem cells or pancreatic cancer cells derived using the same technological platform. For vaccination, induced lung cancer cells were infected with oncolytic Adenovirus or Vaccinia virus, to act as vaccine adjuvants, prior to delivery of vaccines sequentially to a murine inducible transgenic model of lung cancer. Application of this Virus-Infected, Reprogrammed Somatic cell-derived Tumor cell (VIReST) regime primed tumor-specific T cell responses that significantly prolonged survival in both subcutaneous post-vaccine challenge models and induced transgenic models of lung cancer, demonstrating that stem cell-derived prophylactic vaccines may be a feasible intervention for treatment or prevention of lung cancer development in at-risk individuals.